EVA and the controllability-congruence trade-off : an empirical investigation - Jean-Pierre Ponssard; François Larmande (Center for Economic Studies and ifo Institute (CESifo), 2004)
Incentives theory suggests that compensation schemes should be analyzed along two dimensions: controllability and congruence. Most schemes cannot satisfy both criteria at once. EVA bonus schemes, a major managerial innovation of the 90's, favor the congruence criterion. This paper questions ist properties along the controllability dimension. The question is addressed through an in-depth case study: after three years in operation the actual bonuses paid by the system, as well as qualitative feedback from the managers involved, are analyzed. It is argued that EVA bonus schemes may have a major controllability problem.
Keywords: M52; J33; D8; 330; EVA management compensation; controllability-congruence trade-off; compensation standards; Leistungsorientierte Vergütung; Führungskräfte; Betriebliche Wertschöpfung; Leistungsanreiz; Leistungskontrolle